2016
DOI: 10.1152/jn.00959.2015
|View full text |Cite
|
Sign up to set email alerts
|

Na+ current in presynaptic terminals of the crayfish opener cannot initiate action potentials

Abstract: Lin JW. Na ϩ current in presynaptic terminals of the crayfish opener cannot initiate action potentials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
(25 reference statements)
1
5
0
Order By: Relevance
“…To gain a better understanding of mechanisms of USmediated neuromodulation, we studied the biophysical effects of focused US on single motor axons of the crayfish opener neuromuscular junction (Lin 2008(Lin , 2012(Lin , 2013(Lin , 2016. We found two novel phenomena produced by a focused US tone burst in this preparation.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…To gain a better understanding of mechanisms of USmediated neuromodulation, we studied the biophysical effects of focused US on single motor axons of the crayfish opener neuromuscular junction (Lin 2008(Lin , 2012(Lin , 2013(Lin , 2016. We found two novel phenomena produced by a focused US tone burst in this preparation.…”
Section: Discussionmentioning
confidence: 98%
“…VGCs appeared to play a minimal role in US-induced depolarization, since it was still detectable after the main VGCs in this preparation were blocked. Specifically, 1 M TTX, which blocks sodium channels, 200 M 4-AP, which blocks the dominant low-threshold potassium channels, and 50 M ZD7288, which blocks hyperpolarization-activated cation channels, were used to block the main VGCs previously described in the axons (Beaumont and Zucker 2000;Lin 2008Lin , 2012Lin , 2013Lin , 2016. Calcium channels were not blocked because they had been shown to localize in terminal varicosities and to contribute minimally to AP waveform recorded in the axon (Delaney et al 1991;Wojtowicz and Atwood 1984).…”
Section: Figure 1ementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on motor axons of the opener preparation have suggested spatial inhomogeneity of Na + and K + channel densities along the proximo‐distal axis. It has been reported that tetrodotoxin at 1 nM preferentially reduces the excitability of distal branches (Lin, 2013) and that terminal varicosities cannot fire APs by local current injection (Lin, 2016). Furthermore, a 4‐AP sensitive, low voltage‐activated K + channel is concentrated in distal branches, where it is essential for shaping AP amp and duration (Lin, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…If vesicular recycling is the main entry path for LEV, and if the antiepileptic effects of this drug include its actions on ion channels, then, axon excitability should be the first neuronal compartment affected. The opener motor axons of crayfish are accessible to intracellular recording from multiple locations simultaneously, and are ideal for detailed examination of the spatial and temporal factors that contribute to modulation of axonal excitability (Lin, 2012, 2013, 2016). Here, we report the effects of LEV on motor axon excitability and synaptic transmission in the opener preparation.…”
Section: Introductionmentioning
confidence: 99%